Increase in the fructooligosaccharides yield and productivity by solid-state fermentation with Aspergillus japonicus using agro-industrial residues as support and nutrient source - Mussatto, Solange I. (2010)
Corn cobs, coffee silverskin, and cork oak were used as support and nutrient source during the fructooligosaccharides (FOS) production by Aspergillus japonicus, under solid-state fermentation (SSF) conditions. The objectives of this study consisted in evaluating the possibility of improving the FOS yield and productivity, besides to finding an alternative to reduce the production costs, and add value to these agro-industrial residues. Fermentation assays were performed by using the materials as solid support, supplemented or not with nutrients. For comparison, assays were also performed using a synthetic material as solid support, under the same operational conditions. All the material residues acted as nutrient source for the microorganism, since FOS production occurred when all of them were used without nutrient supplementation, but not when the synthetic material was used. Among the evaluated materials, coffee silverskin gave the most interesting fermentation results, with a FOS production similar in both supplemented and non-supplemented media. The elevated FOS production (128.7 g/l) and β-fructofuranosidase activity (71.3 U/ml) obtained by using this material suggest SSF of coffee silverskin with A. japonicus as an interesting and promising strategy to synthesize both products at the industrial level.